Intertidal Canopy‐forming Seaweeds Modulate Understory Seaweed Photoprotective Compounds. Issue 2 (6th February 2021) - Roberts, Emily A.; Bracken, Matthew E.S.
Abstract : Foundation species provide physical structure that enhances the diversity and abundance of associated organisms. Canopy‐forming seaweeds are known to act as foundation species on rocky shores by lowering temperature and desiccation stress. Direct solar radiation, including ultraviolet (UV) light, can also reduce photosynthetic rates in algae, cause oxidative stress and DNA damage. The reduction in UV exposure provided by an algal canopy could therefore be important for understory organisms, including the red alga Chondrus crispus on New England's (USA) rocky shores, and this relationship may be more important at higher tidal elevations with increased low‐tide exposure time. In field experiments, we investigated the relationship between tidal elevation and an index of C. crispus UV exposure, the concentration of UV‐absorbing pigments. Low on the shore, C. crispus grew without a canopy. Higher on the shore, in the mid‐intertidal zone, C. crispus was found under the canopy‐forming rockweed, Fucus distichus subsp. evanescens . At this elevation, C. crispus was shaded (>50%; >1 m above MLLW). We performed a canopy removal experiment that spanned the mid‐zone where C. crispus and F. distichus subsp. evanescens co‐occur and the low‐zone (no canopy). Following canopy removal in the mid‐zone, UV pigment concentrations increased with tidal elevation. After accounting for the effect of elevation, removal of the algal canopy resulted in UV‐protective pigment concentrations 2‐fold higher than in un‐manipulated control plots. These results suggest that amelioration of solar UV exposure might be another mechanism by which canopy seaweeds, acting as foundation species, facilitate understory seaweeds on rocky shores.